Analisis Efisiensi Usahatani Padi Sawah (Studi Kasus di Subak Pacung Babakan, Kecamatan Mengwi, Kabupaten Badung) - I GUSTI AYU CHINTYA DEWI; I KETUT SUAMBA; I G.A.A AMBARAWATI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2012)
ABSTRACT The Efficiency Analysis of Rice Farming Activities (Case Study of Subak Pacung Babakan, Mengwi District, Badung Regency) This study was aimed to determine the use of production factors and constraints faced by farmers in carrying out farming activities in Subak Pacung Babakan, Mengwi District, Badung Regency. Collecting data in this study conducted from November to December 2011. To find out the production factors were analyzed using the equation Cobb-Douglas production function, technical efficiency, price efficiency, and economic efficiency. To know the figure out of constraints experienced from farmers it used qualitative descriptive methods. The results of the research in technical efficiency analysis all of production factors are not efficient and not significantly. The results of pricing efficiency, all these factors there is no efficient production. It also in factors economic efficiency of production is not efficient. That is because of production factors used to excessive, therefore when use of factors production should be reduced to achieve levels of efficiency. The constraints faced are most of the farmers low in their economic and obtain hard to run a farm input. Key words: efficiency, production factors, constraints